Fungal Deoxynivalenol-Induced Enterocyte Distress Is Attenuated by Adulterated Adlay: In Vitro Evidences for Mucoactive Counteraction - Du, Zhimin; Kim, Ki Hyung; Kim, Juil; Moon, Yuseok (Frontiers in Immunology, 2018)
Adlay is a cereal crop that has long been used as traditional herbal medicine and as a highly nourishing food. However, deoxynivalenol (DON), the most prevalent trichothecene mycotoxin worldwide, frequently spoils grains, including adlay, via fungal infection. Based on an assumption that the actions of DON in the gut could be modified by adlay consumption, we simulated the impacts of co-exposure in enterocytes and investigated the effectiveness of treatment with adlay for reducing the risk of DON-induced inflammation and epithelia barrier injury. In particular, adlay suppressed DON-induced pro-inflammatory signals such as mitogen-activated kinase transduction and the epidermal growth factor receptor-linked pathway. In addition to regulation of pro-inflammatory responses, adlay treatment interfered with DON-induced disruption of the epithelial barrier. Mechanistically, adlay could boost activation of protein kinase C (PKC) and cytosolic translocation of human antigen R (HuR) protein, which played critical roles in the epithelial restitution, resulting in protection against disruption of enterocyte barrier integrity. Notably, DON abrogated the Ras homolog gene family member A (RhoA) GTPase-mediated actin cytoskeletal network, which was diminished by adlay treatment in PKC and HuR-dependent ways. Taken together, the present study provides evidences for adlay-based attenuation of trichothecene-induced gut distress, implicating potential use of a new gut protector against enteropathogenic insults in diets.